A Comparative Study of Financial Distress in Sharia-Listed Transportation and Logistics Companies: Insights from the Altman Z - score Model During and After COVID-19 - Muhammad Ramizal Syahidin; Fifi Hakimi; Faricha Maf'ula; Dita Pratiwi Kusumaningtyas; Elvina Assadam (Journal of Islamic Economic Laws, 2026)
This study aims to analyze and compare the financial distress conditions of transportation and logistics sector issuers listed on the Sharia Securities List (Daftar Efek Syariah/DES) using the Altman Z-Score model during and after the COVID-19 pandemic (2021–2024). The novelty of this research lies in the selected period and research object. Employing a quantitative approach, the study examines quarterly financial reports of 14 issuers listed on the Indonesia Stock Exchange (BEI). Data analysis includes descriptive statistics, the Kolmogorov-Smirnov normality test, and the Wilcoxon Signed Rank difference test. The results reveal no statistically significant difference in financial distress levels between the pandemic and post-pandemic periods. Most issuers remained in the Altman Z-Score “red zone,” indicating persistently high bankruptcy risk. Nevertheless, these Sharia-compliant issuers demonstrated considerable financial resilience by consistently maintaining interest-based debt below 45% of total assets in accordance with DES criteria. Government stimulus policies and effective risk management practices further reinforced their stability. This study enriches the Islamic capital market literature by evidencing the relative resilience of Sharia-compliant companies amid prolonged crisis.